Differentiation and its relationship to mental health, psychological and academic adjustment for students of Physical Education - Saeed, Ammar; Ali, Amal; Ahmed, Nada (Journal of Physical Education, 2015)
The research aims to find out all of the differentiation of mental health and psychological and academic adjustment , as well as the relationship between them for the students of the fourth stage in the Faculty of Physical Education of the University of Babylon. This has included the research community on (24) students are in the fourth stage at the College of Physical Education, University of Babylon, the researchers have chosen (20) student of them randomly , and the researchers adopted a descriptive approach survey methods and relationships to fit in correlation with the achievement of planned targets in the search. The researchers chose several benchmarks to achieve the objectives of their research current was tested (differentiation mental) and standard (mental health) and (adapting the school) where they were displayed three measures mentioned in all paragraphs of the gentlemen of experts and specialists (mentioned previously within the personal interviews) have agreed on the validity of these scales paragraphs of so were these standards apply. After verification of the conditions of scientific standards of the three , the researchers applied to the students to show results , most notably marked by students of the fourth stage in the Faculty of Physical Education of the University of Babylon up the middle in the differentiation of mental and varying high in both mental health and adapt the school , as well as the existence of a correlation between mental health and all differentiation of mental and adapt them to the school. Then the researchers recommend a number of recommendations based on what came out of it to deal with the results of the research problem